Evaluación de la gestión administrativa para la mejora de la calidad del servicio del distrito de educación 13d07 Chone Flavio Alfaro - Anchundia Cevallos, Juana Jaqueline (2019)
This research paper analyzes the Administrative Management of the Education District 13D07 Chone-Flavio Alfaro from the legal and administrative point of view taking into consideration the Constitution of the Republic of Ecuador 2008, Organic Law of Public Service, Organic Law of Intercultural Education that will serve of fundamental guidelines for research. A diagnosis of the Administrative Management of Education District 13D07 Chone - Flavio Alfaro will be analyzed through an interview with the director of the education district and the application of the goals per unit form, to detect possible problems and propose solutions, where could verify that in some of the units the total of the goals proposed in the year is not fulfilled, among these units are: Inclusion Support Unit (UDAI) with 53.03% compliance, Human Talent with 77.23 % compliance; Support Monitoring and Regulation with 95.60% compliance and the Citizen Service unit with 94.41% compliance. That is why a proposal for improvement is made to increase the efficiency in the service provided by the Chone Flavio-Alfaro Education District. Finally, conclusions and recommendations regarding the research are proposed.